Investigation of the efficacy and outcomes of intrauterine packing (iup) versus balloon tamponade (bt) in achieving hemostasis in cases of postpartum hemorrhage (pph) unresponsive to conventional medical interventions - Samar Amin; Fatima Abid; Noor Abid; Robina Ali (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVE: Postpartum hemorrhage (PPH) remains a leading cause of maternal morbidity and mortality worldwide. When pharmacologic measures fail, surgical alternatives are required. This study aimed to compare the efficacy and safety of intrauterine packing (IUP) and balloon tamponade (BT) in achieving hemostasis in PPH due to uterine atony. METHODOLOGY: A randomized controlled trial (ClinicalTrials.gov ID: NCT05234578) was conducted at MNCH Hospital, Faisalabad. A total of 220 women aged 18–40 years with primary PPH due to uterine atony were randomized into two groups: Group A (IUP) and Group B (BT). Outcomes included success in achieving hemostasis, complication rates, and blood loss. RESULTS: Mean age and estimated blood loss were comparable between groups (p > 0.05). Although BT had a higher success rate (97.3%) than IUP (91.8%), the difference was not statistically significant (p = 0.135, Fisher’s Exact Test). Perforation occurred more frequently in the IUP group (5.5%) than the BT group (0.9%), but this was also not significant (p = 0.119). Fever and hysterectomy rates showed no significant differences (p > 0.05). CONCLUSION: Although BT showed trends toward greater efficacy and fewer complications than IUP, these differences were not statistically significant. However, due to its minimally invasive nature and favorable safety profile, BT may be considered a preferred option for managing PPH due to uterine atony. Further large-scale studies are warranted.